1996
DOI: 10.1089/aid.1996.12.507
|View full text |Cite
|
Sign up to set email alerts
|

Drug Combinations and Effect Parameters of Zidovudine, Stavudine, and Nevirapine in Standardized Drug-Sensitive and Resistant HIV Type 1 Strains*

Abstract: Reference strains of HIV-1 from the NIH AIDS Research and Reference Reagent Program, including wild-type IIIB, G762-3, and AZT resistant with RT 215T-->Y (G910-11/AZT); 67D-->N, 70K-->R, 215T-->F, 219K-->Q (G691-2/AZT); as well as nevirapine (NEV) resistant with 181Y-->C (N119/NEV); and 103K-->N, 181Y-->C (A17/NEV), were subjected to quantitative parametric efficacy analysis using AZT, stavudine (D4T), and nevirapine (NEV) singly or in combinations in MT4 or MT2 cells. The median-effect principle and combinati… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

4
13
0

Year Published

1997
1997
2014
2014

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 26 publications
(17 citation statements)
references
References 38 publications
4
13
0
Order By: Relevance
“…Second, we have determined that our results are in agreement with those that have been published previously. For example, with the combination of efavirenz and AZT-TP, we have obtained results similar to those obtained by Carroll et al (3) (Table 2); and we found that the combination of AZT and d4T acted additively in the HIV-1 RT enzyme assay and antagonistically in the virus replication assay (data not shown), in agreement with the results of Hoggard et al (13) and Zhu et al (28). Finally, we tested efavirenz in combination with itself and found that it acted, as expected, additively to inhibit both HIV-1 RT function in the enzyme assay and HIV-1 replication in the yield reduction assay (data not shown).…”
Section: Discussionsupporting
confidence: 92%
See 2 more Smart Citations
“…Second, we have determined that our results are in agreement with those that have been published previously. For example, with the combination of efavirenz and AZT-TP, we have obtained results similar to those obtained by Carroll et al (3) (Table 2); and we found that the combination of AZT and d4T acted additively in the HIV-1 RT enzyme assay and antagonistically in the virus replication assay (data not shown), in agreement with the results of Hoggard et al (13) and Zhu et al (28). Finally, we tested efavirenz in combination with itself and found that it acted, as expected, additively to inhibit both HIV-1 RT function in the enzyme assay and HIV-1 replication in the yield reduction assay (data not shown).…”
Section: Discussionsupporting
confidence: 92%
“…The best example is the combination of AZT and d4T. Although there is some disagreement in the literature whether this combination acts additively or antagonistically in an in vitro cell-based system to inhibit HIV-1 replication (13,20,28), this combination has been shown to interact antagonistically with the cellular thymidine kinase (13). The different results seen in the two HIV-1 replication systems are believed to be due more to differences in the concentrations and the ratios of the compounds tested than to a difference in the cell types or virus strains used (12; Merrill et al, reply).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The d4T-AZT-RBV combination was tested as an antagonism control, since previous reports have shown RBV-d4T to be strongly antagonistic (25,26), RBV-AZT to be strongly antagonistic (25), and d4T-AZT to be additive to antagonistic (27,28). The triple combination d4T-AZT-RBV showed strong antagonism, with a mean CI value of Ͼ5.9.…”
Section: Resultsmentioning
confidence: 99%
“…They have synergistic activity with nucleoside reverse transcriptase inhibitors (NRTIs) (7,9,35), high potency that is comparable to that of protease inhibitors (PIs) (27,29,30), proven durability (K. Tashima, S. Staszewski, M. Nelson, A. Rachlis, D. Skiest, R. Stryker, L. Bessen, V. Wirtz, S. Overfield, and D. Sahner, Abstr. XV Int.…”
mentioning
confidence: 99%